Repeated Courses of Radiosurgery for New Brain Metastases to Defer Whole Brain Radiotherapy: Feasibility and Outcome With Validation of the New Prognostic Metric Brain Metastasis Velocity - Fritz, Corinna; Borsky, Kim; Stark, Luisa S.; Tanadini-Lang, S.; Kroeze, Stephanie G. C.; Krayenbühl, Jérôme; Guckenberger, Matthias; Andratschke, Nicolaus (Frontiers in Oncology, 2018)
Purpose: Stereotactic radiosurgery (SRS) is the preferred primary treatment option for patients with a limited number of asymptomatic brain metastases. In case of relapse after initial SRS the optimal salvage treatment is not well defined. Within this retrospective analysis, we investigated the feasibility of repeated courses of SRS to defer Whole-Brain Radiation Therapy (WBRT) and aimed to derive prognostic factors for patient selection. Material and Methods: From 2014 until 2017, 42 patients with 197 brain metastases have been treated with multiple courses of SRS at our institution. Treatment was delivered as single fraction (18 or 20Gy) or hypo-fractionated (6 fractions with 5Gy) radiosurgery. Regular follow-up included clinical examination and contrast-enhanced cMRI at 3 to 4 months’ intervals. Besides clinical and treatment related factors, brain metastasis velocity (BMV) as a newly described clinical prognostic metric was included and calculated between first and second treatment. Results: A median number of 1 lesion (range: 1-13) per course and a median of 2 courses (range: 2-6) per patient were administered resulting in a median of 4 (range: 2-14) metastases treated over time per patient. The median interval between SRS courses was 5.8 months (range: 0.9-35 months). With a median follow-up of 17.4 months (range: 4.6 – 45.5 months) after the first course of treatment, a local control rate of 84% was observed after 1 year and 67% after 2 years. Median time to out-of-field-brain-failure was 7 months (95%CI 4-8 months). WBRT as a salvage treatment was eventually required in 7 patients (16.6%). Median overall survival (OS) has not been reached. Grouped by ds-GPA (≤2 vs. >2) the survival curves showed a significant split (p=0.039). OS differed also significantly between BMV-risk groups when grouped into low vs. intermediate/high risk groups (p=0.025). No grade 4 or 5 acute or late toxicity was observed. Conclusion: In selected patients with relapse after SRS for brain metastases, repeat courses of SRS were safe and minimized the need for rescue WBRT. The innovative, yet easy to calculate metric BMV may facilitate treatment decisions as a prognostic factor for OS.